Building Trust through Public Health: How TMII Can Reimagine Health Tourism Post – Covid 19 - Hadawiyah, Robiyatul; Wijirahayu, Suciana; Aini, Qurrota Nurul; Maulani, Hilma Amalia; Kharisma, Rona Nurul (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2025)
Tourists one sector which is most hit by restrictions which are enforced by Lots country. Dissemination of Covid-19 pushed the government to take various policies to reduce transmission of the Covid-19 virus and concentration of people in society. One of them is closure policy place tourism throughout Indonesia that has an impact on businessmen of the tourist industry. One of the places tourism that completely renovated is Taman Mini Indonesia Indah (TMII) in East Jakarta. Knowledge measurement was carried out qualitatively using literature study. After the survey and education about CHSE tourism health promotion for TMII managers, the results showed a change in knowledge in almost all participants understanding the CHSE assessment instrument and using it as a guide for TMII managers to remain consistent in providing maximum service standards in order to comply with health protocol standards in the post-pandemic era, In order to restore public trust by providing a sense of security and comfort, TMII management ensures that tourism sector workers have received complete vaccines and comply with health protocols. To create a clean, healthy, safe and comfortable tourism sector, Cleanliness, Health, Safety & Environment Sustainability (CHSE) certification is very important for tourism sector businesses for implementation.